THE FUTURE OF VIRTUAL REALITY IN EDUCATION - Munisa Nazirova (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Virtual reality (VR) has rapidly emerged as a groundbreaking technology with the potential to revolutionize various industries, including education. By creating immersive and interactive experiences, VR has the power to transform traditional learning methods and open up a world of possibilities for students. In this article, we will explore the future of virtual reality in education and its potential implications.